Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1589/jpts.24.549
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic Activity of the Lower Limb Muscles during <i>Salat</i> and Specific Exercises

Abstract: Abstract. [Purpose] This study investigated the activity of the rectus femoris (RF), biceps femoris (BF), tibialis anterior (TA) and gastrocnemius (Gas) muscles of healthy subjects during salat and specific exercises using surface electromyography (EMG).[Methods] A group of undergraduates aged between 19 to 25 years voluntarily participated in this study. For the assessment of the RF muscle, the subjects were asked to perform salat movement [standing to prostration (STP)] and squat exercise (SE) and for the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…To describe the mathematical relation between work done and EMG potential value of BF and MG muscles, we have to achieve more accuracy of the measured results and a nonlinear curve fitting is performed on the measured data. From linear regression analysis, we have estimated a mathematical relationship between work done and corresponding EMG potential generated from BF and MG muscle are given in following (6) and (7), respectively. According to our proposed mathematical model, we have calculated the EMG potential for each of the weight associated work done.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To describe the mathematical relation between work done and EMG potential value of BF and MG muscles, we have to achieve more accuracy of the measured results and a nonlinear curve fitting is performed on the measured data. From linear regression analysis, we have estimated a mathematical relationship between work done and corresponding EMG potential generated from BF and MG muscle are given in following (6) and (7), respectively. According to our proposed mathematical model, we have calculated the EMG potential for each of the weight associated work done.…”
Section: Resultsmentioning
confidence: 99%
“…The survey of muscle and joint forces in the human lower extremity during rising motion is performed in [5]. Authors in [6]- [7], investigated EMG activity of the lower limb muscles such as medial gastrocnemius, lateral gastrocnemius muscle, etc. during salat and specific exercises.…”
Section: Introductionmentioning
confidence: 99%
“…Strengthening stroke survivors' religious beliefs may aid them in coping with their disability by providing new meaning to their lives and lessening their emotional distress [74,77]. Furthermore, as the Islamic practice of the salah involves bodily movements, some studies have suggested that the salah could help with cerebral blood flow and postural reflexes [78,79].…”
Section: Implications For Practicementioning
confidence: 99%
“…An example of flexibility exercises is stretching which helps to loosen up the muscles and joints. Many researchers have reported the benefits of exercise from different perspectives [2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Ibrahim et al 6) also evaluated the EMG activities of the lower limb muscles (biceps and rectus femoris, grastrocnemius and lumbar spine) in the different Salat positions and found that all the muscles were activated during Salat's movements. Mohd Safee et al 4) had compared the activities of the human lower limb muscles between Salat and specific exercises and found that Salat is useful for rehabilitation programs. An investigation of body composition resulting during the performance of Salat taraweeh (a special prayer performed by the Muslims only during Ramadhan, the fasting month of the Muslim calendar) showed that it offers benefits to overall human health 14) .…”
Section: Introductionmentioning
confidence: 99%